NEW DEVELOPMENT SOCIETY WITH LIMITED LIABILITY SCIENTIFIC-PRODUCTION ENTERPRISE «ES POLIMER»FOR ELECTRIFIED RAILWAYS - Shumilov, Yu. M. (Science and Transport Progress, 2006)
New developments of polymeric constructions for the electrified railways are considered in the article.